New Insights on the Sequence Stratigraphic Architecture of the Dakota Formation in Kansas–Nebraska–Iowa from a Decade of Sponsored Research Activity - Ludvigson, Greg A.; Witzke, Brian J.; Joeckel, R. M.; Ravn, Robert L.; Phillips, Preston Lee; Gonzalez, Luis A.; Brenner, Robert L. (Current Research in Earth Sciences, 2010)
The Cretaceous Dakota Formation in the areas of Kansas, Nebraska, and Iowa contains a rich and well-preserved microflora of fossil palynomorphs. A comprehensive listing of these taxa is presented in this publication as part of a continuing effort to develop a refined biostratigraphic scheme for mid-Cretaceous terrestrial deposits in North America. The Dakota Formation in this region contains four distinctive Albian-Cenomanian palynostratigraphic zones that are used to partition the unit into successive depositional cycles, and each zone records deposition in fluvial-estuarine environments. The late Albian Kiowa-Skull Creek depositional cycle at the base of the Dakota Formation is recognized throughout the study area, and is also recognized in other parts of the Cretaceous North American Western Interior basin. The overlying newly recognized latest Albian "Muddy-Mowry Cycle" is formally defined for the first time in this paper and correlates with depositional cycles recognized by other workers in other parts of the Western Interior basin. The Cenomanian lower Greenhorn Cycle is already widely recognized by many other workers throughout the Western Interior basin. Laterally extensive thin zones of pervasive carbonate mineral cementation are noted in fluvial-estuarine deposits in the Dakota Formation. They are believed to have formed as synsedimentary cements that precipitated below estuarine marine-flooding surfaces in settings related to discharging paleoground waters. The existence of these early diagenetic cementation zones has important implications for the recognition of diagenetic barriers and baffles to modern fluid flow in the Dakota Formation. New stable isotopic data on these authigenic cements are reported in this paper and add to a body of published data on the δ18O of mid-Cretaceous paleoprecipitation in North America.